Teachers’ Effectiveness and its Influence on Students’ Learning - Kola, Aina Jacob; Sunday, Olanipekun Shola; Ayinde, Garuba Ismaila (Advances in Social Sciences Research Journal, 2015)
The main thrust of this review is the perceived central position of professional focus to the effectiveness of any category of teacher in Nigeria. According to literature, indicators like instructional delivery, students’ assessment, learning environment, teachers’ personal quality, motivation, and subject-content- knowledge among others were used to measure teachers’ effectiveness. Distraction, professional development, interpersonal relationship and punctuality were seen as essential components of professional focus that determines teachers’ effectiveness. Recommendations suggested were based upon these components of professional focus.